Pemanfaatan PhET colorado untuk meningkatkan hasil belajar siswa pada materi rangkaian listrik - Kurniawan, Ade; Herlinawati, Herlinawati; Marasabessy, Rosida (Asian Journal Collaboration of Social Environmental and Education, 2024)
The background of this research is due to the low results of science learning on electrical circuit material. This is because there are no teaching aids for electrical circuit material and teachers are not yet innovative. Hence, they still use the lecture method so that students cannot understand science learning in electrical material. This research aims to improve the learning outcomes of class VI students at SD IT Ar-Rahman Jati Agung regarding the material on the similarities and differences between series and parallel electrical circuits by utilizing PhET Colorado. The research subjects were 19 grade 6 students at SD IT Ar-Rahman. Data collection techniques use test techniques and observation sheets. The research results show that using PhET Colorado media can improve student learning outcomes. This is proven by using this media, student learning outcomes have improved. The percentage of students who reached the KKM in the pre-cycle was 42.1% to 73.7%. In the second cycle, the percentage of students' KKM achievement was 84.2% with an average score of 81. So here, PhET Colorado media can help improve student learning outcomes.